Formation of chromium hydride in chromium being electrodeposited alloyed with hydrogen - Гирин, Олег Борисович; Захаров, Игорь Демьянович (Eastern-European Journal of Enterprise Technologies, 2014)
The aim of the work was experimental verification of validity of the recently discovered phenomenon of phase formation through a stage of liquid state in metals being electrodeposited. The idea of the work was based on the known fact, that during crystallization of liquid phase of a transitional metal (e.g. chromium) alloyed in significant concentration with non-metal of minor atomic radius (e.g. hydrogen) intermediate phases with simple crystal lattices (e.g. hydrides) appear. Therefore, if in electrodeposited chromium alloyed with hydrogen the chromium hydride will be detected, this result will indicate validity of the phenomenon of phase formation through a stage of liquid state in metals being electrodeposited. To find the variants of chromium alloying with hydrogen during its electrodeposition the method for estimation of the degree of hydrogen saturation of metals being electrodeposited was developed. Electrodeposition of chromium was accomplished in such conditions where the volume of hydrogen being formed on the cathode was 62700 times higher than the volume of chromium being formed, which indicated alloying of chromium during its electrodeposition with hydrogen in significant concentration. On the basis of the accomplished experiments the formation of chromium hydride during electrodeposition of chromium alloyed with hydrogen was found. The conclusion, that existence of intermediate phases in electrodeposited metals is a result of crystallization of liquid metallic phase being formed during electrochemical deposition of metals, was made. The obtained result proves the validity of the phenomenon of phase formation through a stage of liquid state in metals being electrodeposited.